A method for improving the density of electroplated copper layer on NdFeB substrate

By adding 3-picolinic acid and a mixture of 3-picolinic acid and 3-picolinammonium hydrochloride to the electroplated copper layer of neodymium iron boron magnet as additives, the problem of poor density of the electroplated copper layer is solved, and a more uniform copper layer deposition and better corrosion resistance are achieved.

CN119145016BActive Publication Date: 2025-03-18BAOTOU INST MAGNETIC NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411667488.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-18
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The thickness of the electroplated copper layer is small and has poor density, resulting in poor corrosion resistance, especially when the thickness of the high and low current zones is large.

Method used

Add a mixture of 3-picolinic acid and 3-picolinyl ammonium hydrochloride as an additive to the copper plating solution to promote the uniform deposition of metal ions on the surface of the substrate and reduce the thickness difference between high and low current regions.

Benefits of technology

The uniformity of the thickness distribution of the copper layer is improved, the density of the electroplated copper layer is enhanced, and its corrosion resistance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119145016B_ABST
    Figure CN119145016B_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the compactness of electroplated copper layer on NdFeB substrate, relates to the technical field of surface treatment, when electroplating copper on NdFeB substrate, an additive is added to the copper plating solution, the additive is a mixture of 3-picolinic acid and 3-picolinyl ammonium and pyridine hydrochloride, the mass ratio of the mixture of 3-picolinic acid and 3-picolinyl ammonium to pyridine hydrochloride is between 1:10 and 10:1, wherein the concentration of the mixture of 3-picolinic acid and 3-picolinyl ammonium is 1-20g / L. The additive of the present invention promotes the uniform deposition of metal ions on the surface of the substrate, and can reduce the thickness difference of high and low current zones of NdFeB magnet during electroplating, thereby improving the uniformity of the copper layer thickness distribution, thereby improving the compactness of the electroplated copper layer as a whole, and then improving the corrosion resistance of the copper layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of surface treatment, in particular to a method for improving the compactness of an electroplated copper layer on a NdFeB substrate. Background Art

[0002] Neodymium iron boron magnets are functional materials widely used in the field of electronic devices. They have active chemical properties and are easily corroded. Currently, they are mostly protected by a surface electroplated nickel layer. In order to improve the bonding strength between the plating layer and the substrate and reduce the damage to the magnet caused by hydrogen evolution reaction during nickel electroplating, it is generally necessary to first electroplate a copper base layer on the surface. In some special application scenarios, the total copper layer thickness obtained by the first two electroplatings is required to be relatively thin (usually required to be less than or equal to 5 microns). During the electroplating process, the current is unevenly distributed on the workpiece, with high and low positions, resulting in uneven thickness of the electroplated copper layer. The thickness of the electroplated copper layer in the low current area is less than or even much less than the nominal thickness (5 microns). When the thickness of the electroplated copper layer is very small, the density of the copper layer has poor corrosion resistance for the entire magnet. Therefore, the present invention aims to reduce the thickness difference between the high and low current areas, improve the uniformity of the copper layer thickness distribution, thereby improving the overall density of the electroplated copper layer, and further improving the corrosion resistance of the copper layer. Summary of the invention

[0003] The object of the present invention is to provide a method for improving the compactness of an electroplated copper layer on a NdFeB substrate, which can improve the uniformity of the thickness distribution of the electroplated copper layer, thereby improving the overall compactness of the electroplated copper layer and improving its corrosion resistance.

[0004] To achieve the above object, the solution of the present invention is:

[0005] A method for improving the compactness of an electroplated copper layer on a neodymium iron boron substrate. When electroplating copper on the surface of the neodymium iron boron substrate, an additive is added to a copper plating solution. The additive is a mixture of 3-picolinic acid, 3-picolinyl ammonium and pyridine hydrochloride. The mass ratio of the mixture of 3-picolinic acid and 3-picolinyl ammonium to pyridine hydrochloride is between 1:10 and 10:1, and the concentration of the mixture of 3-picolinic acid and 3-picolinyl ammonium is between 1 and 20 g / L.

[0006] Further, the following steps are included:

[0007] Step S10: Placing the NdFeB substrate in a first copper plating solution for electroplating to perform pre-copper plating to form a pre-copper plating layer on the surface of the NdFeB substrate, wherein the first copper plating solution contains an additive, the additive is a mixture of 3-pyridinecarboxylic acid, 3-pyridinecarboxylic acid ammonium and pyridine hydrochloride, the mass ratio of the mixture of 3-pyridinecarboxylic acid and 3-pyridinecarboxylic acid ammonium to pyridine hydrochloride is between 1:10 and 10:1, wherein the concentration of the mixture of 3-pyridinecarboxylic acid and 3-pyridinecarboxylic acid ammonium is between 1-20 g / L;

[0008] Step S20: Placing the pre-copper-plated NdFeB substrate in a second copper plating solution for electroplating to perform thick copper plating to form a thick copper plating layer on the surface of the pre-copper plating layer, wherein the second copper plating solution contains an additive, wherein the additive is a mixture of 3-pyridinecarboxylic acid, 3-pyridinecarboxylic acid ammonium and pyridine hydrochloride, wherein the mass ratio of the mixture of 3-pyridinecarboxylic acid and 3-pyridinecarboxylic acid ammonium to pyridine hydrochloride is between 1:10 and 10:1, wherein the concentration of the mixture of 3-pyridinecarboxylic acid and 3-pyridinecarboxylic acid ammonium is between 1-20 g / L;

[0009] Step S30: placing the thickened copper-plated NdFeB substrate in a chemical nickel plating solution to form a nickel-phosphorus alloy layer on the surface of the thickened copper-plated layer, or placing the thickened copper-plated NdFeB substrate in an electroplating nickel-phosphorus alloy solution to form a nickel-phosphorus alloy layer on the surface of the thickened copper-plated layer.

[0010] Further, in step S10, the mass concentration of each chemical component in the first copper plating solution is as follows:

[0011] Copper ion: 1.5-2.5 g / L;

[0012] HEDP: 80-150g / L;

[0013] Potassium carbonate: 20-80g / L;

[0014] Potassium hydroxide: 20-100g / L;

[0015] Additive: the mass ratio of the mixture of 3-picolinic acid and 3-picolinamide to pyridine hydrochloride is between 1:5 and 5:1, and the concentration of the mixture of 3-picolinic acid and 3-picolinamide is between 1-10 g / L;

[0016] The copper ions are obtained by dissolving a copper-containing inorganic salt during solution preparation, wherein the copper-containing inorganic salt is selected from at least one of copper sulfate, copper acetate and copper carbonate.

[0017] Furthermore, in step S10, the pre-copper plating temperature is 10-25°C, the pH value is 9-12, and the anode electrode is a phosphor copper anode or an oxygen-free copper anode; when roller plating is used, the current density is 0.1-0.3A / square decimeter; when rack plating is used, the current density is 0.2-1.0A / square decimeter.

[0018] Further, in step S20, the mass concentration of each chemical component in the second copper plating solution is as follows:

[0019] Copper ion: 6-12g / L;

[0020] HEDP: 80-200g / L;

[0021] Potassium carbonate: 20-80g / L;

[0022] Potassium hydroxide: 20-100g / L;

[0023] Brightener: 5-15ml / L;

[0024] Auxiliary agent: 5-15ml / L;

[0025] Additives: The mass ratio of the mixture of 3-pyridinecarboxylic acid and 3-pyridinecarboxylic acid ammonium to pyridine hydrochloride is between 1:5 and 5:1, and the concentration of the mixture of 3-pyridinecarboxylic acid and 3-pyridinecarboxylic acid ammonium is between 1-10 g / L.

[0026] Furthermore, in step S20, the temperature of the thickened copper plating is 40-60°C, the pH value is 8-10, and the anode electrode is a phosphor copper anode or an oxygen-free copper anode; when roller plating is used, the current density is 0.1-2.0A / square decimeter; when rack plating is used, the current density is 0.5-4.0A / square decimeter.

[0027] Further, in step S30, when the thickened copper-plated NdFeB substrate is placed in a chemical nickel plating solution, the mass concentration of each chemical component in the chemical nickel plating solution is as follows:

[0028] Nickel sulfate: 20-25g / L;

[0029] Sodium hypophosphite: 25-30g / L;

[0030] Citric acid: 10-15 g / L;

[0031] Malic acid: 8-12 g / L;

[0032] Lactic acid: 8-10 g / L;

[0033] Ammonia: 10-15ml / L;

[0034] Stabilizer: 1-5mg / L;

[0035] The temperature of the chemical nickel plating solution is 75-90°C and the pH value is 4.6-5.0.

[0036] Further, in step S30, when the thickened copper-plated NdFeB substrate is placed in the electroplating nickel-phosphorus alloy solution, the mass concentration of each chemical component in the electroplating nickel-phosphorus alloy solution is as follows:

[0037] Nickel sulfate: 250-400g / L;

[0038] Sodium hypophosphite: 80-100ml / L;

[0039] Sodium citrate: 50g / L;

[0040] Brightener and anti-pinhole agent: 80-100 ml / L;

[0041] The temperature of the electroplating phosphorus alloy solution is 50-70°C and the pH value is 2.3-3.2.

[0042] Further, after step S10 is completed, the thickness d of the pre-plated copper layer Cu1 = 0.5-2.5 microns; after step S20 is completed, the thickness of the copper plating layer is thickened d Cu2 = 1-10 microns; after step S30 is completed, the thickness of the nickel-phosphorus alloy layer d NiP =1-10 microns.

[0043] Further, after step S20 is completed, the thickness of the copper plating layer is increased to d Cu2 = 1-3 microns; after step S30 is completed, the thickness of the nickel-phosphorus alloy layer d NiP =1-3 microns; total coating thickness d 总 =d Cu1 +d Cu2 +d NiP ≤6 microns.

[0044] After adopting the above scheme, the beneficial effects of the present invention are:

[0045] When electroplating a copper layer on a neodymium iron boron substrate, the present invention adds an additive to a copper plating solution: a mixture of 3-picolinic acid, 3-picolinyl ammonium and pyridine hydrochloride, and the mass ratio of the mixture of 3-picolinic acid and 3-picolinyl ammonium to pyridine hydrochloride is between 1:10 and 10:1, wherein the concentration of the mixture of 3-picolinic acid and 3-picolinyl ammonium is 1-20 g / L, and a quantitative additive promotes uniform deposition of metal ions on the surface of the substrate, which can reduce the thickness difference between high and low current areas of the neodymium iron boron magnet during electroplating, thereby improving the uniformity of the copper layer thickness distribution, thereby improving the overall compactness of the electroplated copper layer, and further improving the corrosion resistance of the copper layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 This is a photo of the copper-plated NdFeB workpiece of Comparative Example 1 of the present invention;

[0047] Figure 2 This is a photo of a copper-plated NdFeB workpiece according to Example 1 of the present invention;

[0048] Figure 3 This is a photo of a hundred-grid test of a copper-plated NdFeB workpiece in Comparative Example 1 of the present invention;

[0049] Figure 4 This is a photo of a hundred-grid test of a copper-plated NdFeB workpiece according to Example 1 of the present invention;

[0050] Figure 5 This is a photo of a hundred-grid test of a copper-plated NdFeB workpiece according to Example 2 of the present invention;

[0051] Figure 6 This is a photo of a hundred-grid test of a copper-plated NdFeB workpiece according to Example 3 of the present invention;

[0052] Figure 7 This is a photo of a hundred-grid test of a copper-plated NdFeB workpiece according to Example 4 of the present invention;

[0053] Figure 8 This is a salt spray test photo of the nickel-phosphorus plating of Comparative Example 1 of the present invention;

[0054] Fig. 9 These are salt spray test photos of Examples 1-4 of the present invention after nickel-phosphorus plating, and from left to right they are Examples 1-4. DETAILED DESCRIPTION

[0055] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0056] like Figures 1 to 9 As shown, this embodiment provides a method for improving the compactness of the electroplated copper layer on the NdFeB substrate. When electroplating copper on the surface of the NdFeB substrate, an additive is added to the copper plating solution. The additive is a mixture of 3-picolinic acid, 3-picolinamide and pyridine hydrochloride. The mass ratio of the mixture of 3-picolinic acid and 3-picolinamide to pyridine hydrochloride is between 1:10 and 10:1, and the concentration of the mixture of 3-picolinic acid and 3-picolinamide is 1-20 g / L.

[0057] When electroplating a copper layer on a neodymium iron boron substrate, the present invention adds an additive to a copper plating solution: a mixture of 3-picolinic acid, 3-picolinyl ammonium and pyridine hydrochloride, and the mass ratio of the mixture of 3-picolinic acid and 3-picolinyl ammonium to pyridine hydrochloride is between 1:10 and 10:1, wherein the concentration of the mixture of 3-picolinic acid and 3-picolinyl ammonium is 1-20 g / L, and a quantitative additive promotes uniform deposition of metal ions on the surface of the substrate, which can reduce the thickness difference between high and low current areas of the neodymium iron boron magnet during electroplating, thereby improving the uniformity of the copper layer thickness distribution, thereby improving the overall compactness of the electroplated copper layer, and further improving the corrosion resistance of the copper layer.

[0058] Furthermore, the method further comprises the following steps:

[0059] Step S10: Placing the NdFeB substrate in a first copper plating solution for electroplating to perform pre-copper plating to form a pre-copper plating layer on the surface of the NdFeB substrate, wherein the first copper plating solution contains an additive, the additive is a mixture of 3-pyridinecarboxylic acid, 3-pyridinecarboxylic acid ammonium and pyridine hydrochloride, the mass ratio of the mixture of 3-pyridinecarboxylic acid and 3-pyridinecarboxylic acid ammonium to pyridine hydrochloride is between 1:10 and 10:1, wherein the concentration of the mixture of 3-pyridinecarboxylic acid and 3-pyridinecarboxylic acid ammonium is between 1-20 g / L;

[0060] Step S20: Placing the pre-copper-plated NdFeB substrate in a second copper plating solution for electroplating to perform thick copper plating to form a thick copper plating layer on the surface of the pre-copper plating layer, wherein the second copper plating solution contains an additive, wherein the additive is a mixture of 3-pyridinecarboxylic acid, 3-pyridinecarboxylic acid ammonium and pyridine hydrochloride, wherein the mass ratio of the mixture of 3-pyridinecarboxylic acid and 3-pyridinecarboxylic acid ammonium to pyridine hydrochloride is between 1:10 and 10:1, wherein the concentration of the mixture of 3-pyridinecarboxylic acid and 3-pyridinecarboxylic acid ammonium is between 1-20 g / L;

[0061] Step S30: placing the thickened copper-plated NdFeB substrate in a chemical nickel plating solution to form a nickel-phosphorus alloy layer on the surface of the thickened copper-plated layer, or placing the thickened copper-plated NdFeB substrate in an electroplating nickel-phosphorus alloy solution to form a nickel-phosphorus alloy layer on the surface of the thickened copper-plated layer;

[0062] Specifically, pre-copper plating, thickened copper plating and nickel-phosphorus alloy plating are performed on the NdFeB substrate to form a composite layer on the NdFeB substrate to effectively protect the NdFeB substrate from environmental corrosion.

[0063] Specifically, in step S10, the mass concentration of each chemical component in the first copper plating solution is as follows:

[0064] Copper ion: 1.5-2.5g / L;

[0065] HEDP: 80-150g / L;

[0066] Potassium carbonate: 20-80g / L;

[0067] Potassium hydroxide: 20-100g / L;

[0068] Preferably, the additive: the mass ratio of the mixture of 3-picolinic acid and 3-picolinamide to pyridine hydrochloride is between 1:5 and 5:1, and the concentration of the mixture of 3-picolinic acid and 3-picolinamide is between 1-10 g / L.

[0069] Specifically, the copper ions are obtained by dissolving a copper-containing inorganic salt during solution preparation, and the copper-containing inorganic salt is selected from at least one of copper sulfate, copper acetate, and copper carbonate.

[0070] Specifically, in step S10, the pre-copper plating temperature is 10-25°C, the pH value is 9-12, and the anode electrode is a phosphor copper anode or an oxygen-free copper anode; when roller plating is used, the current density is 0.1-0.3A / square decimeter; when rack plating is used, the current density is 0.2-1.0A / square decimeter.

[0071] Specifically, in step S20, the mass concentration of each chemical component in the second copper plating solution is as follows:

[0072] Copper ion: 6-12g / L;

[0073] HEDP: 80-200g / L;

[0074] Potassium carbonate: 20-80g / L;

[0075] Potassium hydroxide: 20-100g / L;

[0076] Brightener: 5-15ml / L; the brightener is preferably selenium dioxide;

[0077] Auxiliary agent: 5-15ml / L; the auxiliary agent is preferably butynediol;

[0078] Preferably, the additive: the mass ratio of the mixture of 3-pyridinecarboxylic acid and 3-pyridinecarboxylic acid ammonium to pyridine hydrochloride is between 1:5 and 5:1, and the concentration of the mixture of 3-pyridinecarboxylic acid and 3-pyridinecarboxylic acid ammonium is between 1-10 g / L.

[0079] Furthermore, in step S20, the temperature of the thickened copper plating is 40-60°C, the pH value is 8-10, and the anode electrode is a phosphor copper anode or an oxygen-free copper anode; when roller plating is used, the current density is 0.1-2.0A / square decimeter; when rack plating is used, the current density is 0.5-4.0A / square decimeter.

[0080] Specifically, in step S30, when the thickened copper-plated NdFeB substrate is placed in a chemical nickel plating solution, the mass concentration of each chemical component in the chemical nickel plating solution is as follows:

[0081] Nickel sulfate: 20-25g / L;

[0082] Sodium hypophosphite: 25-30g / L;

[0083] Citric acid: 10-15 g / L;

[0084] Malic acid: 8-12 g / L;

[0085] Lactic acid: 8-10 g / L;

[0086] Ammonia: 10-15ml / L;

[0087] Stabilizer: 1-5 mg / L, the stabilizer is preferably sodium antimonate;

[0088] Preferably, the temperature of the chemical nickel plating solution is 75-90° C., and the pH value is 4.6-5.0.

[0089] Specifically, in step S30, when the thickened copper-plated NdFeB substrate is placed in a nickel-phosphorus alloy electroplating solution, the mass concentration of each chemical component in the nickel-phosphorus alloy electroplating solution is as follows:

[0090] Nickel sulfate: 250-400g / L;

[0091] Sodium hypophosphite: 80-100ml / L;

[0092] Sodium citrate: 50g / L;

[0093] Brightener and anti-pinhole agent: 80-100 ml / L;

[0094] Preferably, the temperature of the phosphorus alloy electroplating solution is 50-70° C., and the pH value is 2.3-3.2.

[0095] Further, after step S10 is completed, the thickness of the pre-plated copper layer is d Cu1 = 0.5-2.5 microns; after step S20 is completed, the thickness of the copper plating layer is thickened d Cu2 = 1-10 microns; after step S30 is completed, the thickness of the nickel-phosphorus alloy layer d NiP =1-10 microns.

[0096] Preferably, after step S20 is completed, the thickness of the copper plating layer is increased. Cu2 = 1-3 microns; after step S30 is completed, the thickness of the nickel-phosphorus alloy layer d NiP = 1-3 μm;

[0097] Specifically, the total coating thickness d 总 =d Cu1 +d Cu2 +d NiP ≤6 microns.

[0098] Specifically, before step S10, the NdFeB workpiece is processed: the electroplating process is carried out in a 100L test tank, the substrate workpiece is a sintered NdFeB sheet with a size of 12.5×7.9×0.38 (mm), and before the workpiece enters the plating tank, the workpiece must be cleaned and properly activated, which is called pre-treatment. The pre-treatment conditions are as follows:

[0099] The workpiece was cleaned in a 4% nitric acid aqueous solution for 40 seconds, then cleaned in pure water under ultrasonic conditions for 40 seconds, then activated in a 1% sulfuric acid aqueous solution for 20 seconds, and finally cleaned in pure water for 10 seconds;

[0100] Further, in step S10, the NdFeB workpiece is placed in a first copper plating solution for pre-copper plating to form a pre-copper plating layer on the surface of the NdFeB substrate, the pre-copper plating temperature is 19° C., the pH value is 10.4, and the anode electrode is a phosphor copper anode; roller plating is adopted, the current density is 0.2A / square decimeter, and the electroplating time is 100 minutes;

[0101] In the first copper plating solution, the mass concentration of each chemical component is as follows:

[0102] Copper ion: 1.9g / L (copper-containing inorganic salt is copper sulfate);

[0103] HEDP: 105g / L;

[0104] Potassium carbonate: 50g / L;

[0105] Potassium hydroxide 30g / L;

[0106] Further, in step S20, the NdFeB workpiece is placed in a second copper plating solution for thick copper plating to form a thick copper plating layer on the surface of the pre-copper plating layer. The thick copper plating temperature is 50° C., the pH value is 8.8, the anode electrode is a phosphor copper anode, roller plating is used, the current density is 0.3A / square decimeter, and the electroplating time is 120 minutes;

[0107] In the second copper plating solution, the mass concentration of each chemical component is as follows:

[0108] Copper ion: 9.5g / L (copper-containing inorganic salt is copper sulfate);

[0109] HEDP: 150g / L;

[0110] Potassium carbonate: 55g / L;

[0111] Potassium hydroxide: 35g / L;

[0112] Brightener is selenium dioxide: 8ml / L;

[0113] The auxiliary agent is butynediol: 7ml / L;

[0114] During electroplating, additives are added to both the first copper plating solution and the second copper plating solution, represented by A, wherein:

[0115] Example 1: A1=1.0 g (3-picolinic acid) / L+1.0 g (3-picolinamide) / L+0.3 g (pyridine hydrochloride) / L;

[0116] Embodiment 2: A2=2.0g (3-picolinic acid) / L+2.5g (3-picolinamide) / L+1.0g (pyridine hydrochloride) / L;

[0117] Embodiment 3: A3=0.5g (3-picolinic acid) / L+0.5g (3-picolinamide) / L+2.0g (pyridine hydrochloride) / L;

[0118] Embodiment 4: A4=5.0g (3-picolinic acid) / L+0.5g (3-picolinamide) / L+2.0g (pyridine hydrochloride) / L;

[0119] It is understood that 3-picolinamide is a derivative of 3-picolinic acid.

[0120] Furthermore, in step S30, the NdFeB substrate is placed in a chemical nickel plating solution to perform nickel plating to form a nickel-phosphorus alloy layer on the surface of the thickened copper plating layer.

[0121] The mass concentration of each chemical component in the chemical nickel plating solution is as follows:

[0122] Nickel sulfate (hexahydrate): 22g / L;

[0123] Sodium hypophosphite 30g / L;

[0124] Citric acid: 13g / L;

[0125] Malic acid: 8g / L;

[0126] Lactic acid: 8g / L;

[0127] Ammonia water: 10ml / L;

[0128] The stabilizer is sodium antimonate: 2 mg / L;

[0129] The temperature of the chemical nickel plating solution is 86° C., the pH value is 4.6, and the time is 30 minutes.

[0130] Specifically, after step S20, that is, after the thick copper plating is completed, 100 samples are randomly selected for each blue roll and a hundred-grid test is performed; the experimental standard is: ASTM D3002 D3359DIN EN ISO 2409 test, and the judgment standard is: 4B, that is, there is a small piece of peeling at the intersection of the cut, and the actual damage in the grid area does not exceed 5%;

[0131] After the test samples are taken, the process proceeds to step S30, i.e., chemical nickel plating is selected. After the nickel plating is completed, 100 samples are randomly selected from each rolling blue and subjected to a neutral salt spray test. The experimental standard is: GT / T 24.23.17-2008 / IEC 60068-2-11:1981.

[0132] Comparative Example 1:

[0133] In Comparative Example 1, the steps of treating the NdFeB workpiece before step S10 and the nickel plating process of step S30 are the same, except that when step S10 is performed, pre-copper plating is performed, and the mass concentration of each chemical component in the first copper plating solution is as follows:

[0134] Copper ion: 1.9 g / L (copper-containing inorganic salt is copper sulfate);

[0135] HEDP: 105g / L;

[0136] Potassium carbonate: 50g / L;

[0137] Potassium hydroxide 30g / L;

[0138] No additives are added;

[0139] The pre-copper plating temperature was 19°C, the pH value was 10.4, and the anode electrode was a phosphor copper anode; roller plating was adopted, the current density was 0.2A / square decimeter, and the electroplating time was 100 minutes;

[0140] When performing step S20, that is, performing thick copper plating, the mass concentration of each chemical component in the second copper plating solution is as follows:

[0141] Copper ion: 9.5 g / L (copper-containing inorganic salt is copper sulfate);

[0142] HEDP: 150g / L;

[0143] Potassium carbonate: 55g / L;

[0144] Potassium hydroxide: 35g / L;

[0145] Brightener is selenium dioxide: 8ml / L;

[0146] The auxiliary agent is butynediol: 7ml / L.

[0147] No additives are added;

[0148] The temperature of thick copper plating is 50°C, the pH value is 8.8, the anode electrode is a phosphor copper anode, roller plating is adopted, the current density is 0.3A / square decimeter, and the electroplating time is 120 minutes;

[0149] The results of the embodiments and comparative examples are shown in Table 1 and Table 2:

[0150]

[0151]

[0152] like Figure 1 to Figure 2 As shown, Figure 1 This is a photo of a copper-plated NdFeB workpiece of Example 1. No additives were added to the copper plating in Example 1. It can be seen from the photo that the crystals of the coating are relatively large and the surface is relatively rough. Figure 2 This is a photo of the copper-plated NdFeB workpiece of Example 1. Example 1 adds the additive of the present invention. It can be seen from the photo that compared with Figure 1 The crystals in the middle coating are relatively fine, and the surface of the coating is relatively Figure 1 More uniform and smooth; therefore, the additive of the present invention can refine the crystallization of the coating, making the coating surface more uniform and smoother than when no additive is added;

[0153] like Figures 3 to 7 As shown, Figure 3This is a photo of the 100-grid test of the copper-plated NdFeB workpiece of Example 1. No additives were added to Example 1. Figure 4-Figure 7 The following are the hundred-grid test photos of the copper-plated NdFeB workpieces of Examples 1-4, where the additives of the present invention are added to Examples 1-4. Figure 3-Figure 7 All of them are copper-plated NdFeB workpieces that have passed the hundred-grid test and meet the test standards and judgment standards. Therefore, it can be concluded that adding the additive of the present invention has no negative impact compared to not adding the additive.

[0154] Table 1 is a comparison of the test results of the coating parameters of Comparative Example 1 and Examples 1-4. It can be concluded from Table 1 that after adding the additive of the present invention, the average total copper layer thickness in the low zone is increased, and the average total copper layer thickness in the high zone is reduced, so that the difference between the average copper layer thickness in the low zone and the average copper layer thickness in the high zone is reduced, and then the ratio of the average high zone thickness / low zone thickness ratio is reduced, which means that the additive of the present invention can reduce the difference in the thickness of the electroplated copper layer caused by the high and low current zones, and improve the uniformity of the copper layer thickness distribution;

[0155] Table 2 is a comparison of the functional test results of Comparative Example 1 and Examples 1-4. In Table 2, the nominal copper layer thickness of Examples 1-4 is less than the nominal copper layer thickness in Comparative Example 1, and the smaller the thickness of the electroplated copper layer, the worse the corrosion resistance. However, the average high area thickness / low area thickness ratio of the electroplated copper layer of Examples 1-4 is less than the average high area thickness / low area thickness ratio of Comparative Example 1, indicating that the uniformity of the electroplated copper layer of Examples 1-4 is better than that of the electroplated copper layer of Comparative Example 1. After the salt spray test, the proportion of Examples 1-4 that passed the 24-hour neutral salt spray test was higher than the proportion of Comparative Example 1 that passed the 24-hour neutral salt spray test. Therefore, it is shown that the salt spray corrosion resistance of the NdFeB workpiece is related to the uniformity of the thickness distribution of the electroplated copper layer. Combined with Table 1, it is shown that the additive of the present invention can improve the uniformity of the copper layer thickness distribution, thereby improving the compactness of the electroplated copper layer, thereby improving the salt spray corrosion resistance of the electroplated copper layer;

[0156] And combined with Figures 8 to 9 , Figure 8 The circled part is the workpiece corroded by the 24-hour neutral salt spray test in Example 1. Fig. 9 The circled part is the workpiece corroded by Example 1-4 after 24 hours of neutral salt spray test. From left to right, they are Example 1-4. Figures 8 to 9 From the comparison, it can be seen that the number of corroded workpieces in Comparative Example 1 is greater than the total number of corroded workpieces in Examples 1-4, indicating that after adding the additive of the present invention, the performance of salt spray corrosion resistance is better. Therefore, it can also be explained that after adding the additive of the present invention, the density of the electroplated copper layer is improved.

[0157] In summary, the test results in Table 1 and Table 2 show that, under the premise that the thickness of the pre-plated copper layer, the thickened copper plating layer and the nickel-phosphorus alloy layer in the embodiment and the comparative example are similar, the additive reduces the thickness difference between the high and low current areas, improves the uniformity of the thickness distribution of the electroplated copper layer, improves the compactness of the copper layer, and thus improves the performance of salt spray corrosion resistance. Embodiment 1 is preferred.

[0158] The above description is only a preferred embodiment of the present invention and is not a limitation on the design of this case. Any equivalent changes made based on the design key of this case shall fall within the protection scope of this case.

Claims

1. A method for improving the compactness of an electroplated copper layer on a NdFeB substrate, characterized in that: When electroplating copper on the surface of a neodymium iron boron substrate, an additive is added to the copper plating solution, wherein the additive is a mixture of 3-pyridine carboxylic acid, 3-pyridine carboxylic acid ammonium and pyridine hydrochloride, and the mass ratio of the mixture of 3-pyridine carboxylic acid and 3-pyridine carboxylic acid ammonium to pyridine hydrochloride is between 1:10 and 10:1, wherein the concentration of the mixture of 3-pyridine carboxylic acid and 3-pyridine carboxylic acid ammonium is 1-20 g / L; comprising the following steps: Step S10: Placing the NdFeB substrate in a first copper plating solution for electroplating to perform pre-copper plating to form a pre-copper plating layer on the surface of the NdFeB substrate, wherein the first copper plating solution contains an additive, the additive is a mixture of 3-pyridinecarboxylic acid, 3-pyridinecarboxylic acid ammonium and pyridine hydrochloride, the mass ratio of the mixture of 3-pyridinecarboxylic acid and 3-pyridinecarboxylic acid ammonium to pyridine hydrochloride is between 1:10 and 10:1, wherein the concentration of the mixture of 3-pyridinecarboxylic acid and 3-pyridinecarboxylic acid ammonium is between 1-20 g / L; Step S20: Placing the pre-copper-plated NdFeB substrate in a second copper plating solution for electroplating to perform thick copper plating to form a thick copper plating layer on the surface of the pre-copper plating layer, wherein the second copper plating solution contains an additive, wherein the additive is a mixture of 3-pyridinecarboxylic acid, 3-pyridinecarboxylic acid ammonium and pyridine hydrochloride, wherein the mass ratio of the mixture of 3-pyridinecarboxylic acid and 3-pyridinecarboxylic acid ammonium to pyridine hydrochloride is between 1:10 and 10:1, wherein the concentration of the mixture of 3-pyridinecarboxylic acid and 3-pyridinecarboxylic acid ammonium is between 1-20 g / L; Step S30: placing the thickened copper-plated NdFeB substrate in a chemical nickel plating solution to form a nickel-phosphorus alloy layer on the surface of the thickened copper-plated layer, or placing the thickened copper-plated NdFeB substrate in an electroplating nickel-phosphorus alloy solution to form a nickel-phosphorus alloy layer on the surface of the thickened copper-plated layer; In step S10, the mass concentration of each chemical component in the first copper plating solution is as follows: Copper ion: 1.5-2.5g / L; HEDP: 80-150g / L; Potassium carbonate: 20-80g / L; Potassium hydroxide: 20-100g / L; In step S20, the mass concentration of each chemical component in the second copper plating solution is as follows: Copper ion: 6-12g / L; HEDP: 80-200g / L; Potassium carbonate: 20-80g / L; Potassium hydroxide: 20-100g / L; Brightener: 5-15ml / L; Auxiliary agent: 5-15ml / L.

2. A method for improving the compactness of the electroplated copper layer on a NdFeB substrate as claimed in claim 1, characterized in that: In step S10, the mass concentration of the additive in the first copper plating solution is as follows: Additives: The mass ratio of the mixture of 3-picolinic acid and 3-picolinyl ammonium to pyridine hydrochloride is between 1:5 and 5:1, and the concentration of the mixture of 3-picolinic acid and 3-picolinyl ammonium is between 1-10 g / L; The copper ions are obtained by dissolving a copper-containing inorganic salt during solution preparation, wherein the copper-containing inorganic salt is selected from at least one of copper sulfate, copper acetate and copper carbonate.

3. A method for improving the compactness of the electroplated copper layer on a NdFeB substrate as claimed in claim 1, characterized in that: In step S10, the pre-copper plating temperature is 10-25°C, the pH value is 9-12, and the anode electrode is a phosphor copper anode or an oxygen-free copper anode; when roller plating is adopted, the current density is 0.1-0.3A / square decimeter; when rack plating is adopted, the current density is 0.2-1.0A / square decimeter.

4. A method for improving the compactness of the electroplated copper layer on a NdFeB substrate as claimed in claim 1, characterized in that: In step S20, the mass concentration of the additive in the second copper plating solution is as follows: Additives: The mass ratio of the mixture of 3-pyridinecarboxylic acid and 3-pyridinecarboxylic acid ammonium to pyridine hydrochloride is between 1:5 and 5:1, and the concentration of the mixture of 3-pyridinecarboxylic acid and 3-pyridinecarboxylic acid ammonium is between 1-10 g / L.

5. A method for improving the compactness of the electroplated copper layer on a NdFeB substrate as claimed in claim 1, characterized in that: In step S20, the temperature of thick copper plating is 40-60°C, the pH value is 8-10, and the anode electrode is a phosphor copper anode or an oxygen-free copper anode; when roller plating is adopted, the current density is 0.1-2.0A / square decimeter; when rack plating is adopted, the current density is 0.5-4.0A / square decimeter.

6. A method for improving the compactness of the electroplated copper layer on a NdFeB substrate as claimed in claim 1, characterized in that: In step S30, when the thickened copper-plated NdFeB substrate is placed in a chemical nickel plating solution, the mass concentration of each chemical component in the chemical nickel plating solution is as follows: Nickel sulfate: 20-25g / L; Sodium hypophosphite: 25-30g / L; Citric acid: 10-15 g / L; Malic acid: 8-12 g / L; Lactic acid: 8-10 g / L; Ammonia: 10-15ml / L; Stabilizer: 1-5mg / L; The temperature of the chemical nickel plating solution is 75-90°C and the pH value is 4.6-5.

0.

7. A method for improving the compactness of the electroplated copper layer on a NdFeB substrate as claimed in claim 1, characterized in that: In step S30, when the thickened copper-plated NdFeB substrate is placed in a nickel-phosphorus alloy electroplating solution, the mass concentration of each chemical component in the nickel-phosphorus alloy electroplating solution is as follows: Nickel sulfate: 250-400g / L; Sodium hypophosphite: 80-100ml / L; Sodium citrate: 50g / L; Brightener and anti-pinhole agent: 80-100ml / L; The temperature of the electroplating phosphorus alloy solution is 50-70°C and the pH value is 2.3-3.

2.

8. A method for improving the compactness of an electroplated copper layer on a NdFeB substrate as claimed in claim 1, characterized in that: After step S10 is completed, the thickness of the pre-plated copper layer is Cu1 = 0.5-2.5 μm; After step S20 is completed, the thickness of the copper plating layer is increased to d Cu2 = 1-10 microns; After step S30 is completed, the thickness d of the nickel-phosphorus alloy layer Ni P = 1-10 microns.

9. A method for improving the compactness of the electroplated copper layer on a NdFeB substrate as claimed in claim 8, characterized in that: After step S20 is completed, the thickness of the copper plating layer is increased to d Cu2 = 1-3 μm; After step S30 is completed, the thickness d of the nickel-phosphorus alloy layer NiP = 1-3 μm; Total coating thickness d 总 =d Cu1 +d Cu2 +d NiP ≤6 microns.

Citation Information

Patent Citations

  • Electroplating method of ultrathin plating layers for neodymium iron boron

    CN112458502A

  • High-speed copper electroplating solution

    JP1983009996A